How To Transform a Lecturer's Research Interest into a Student-Centered Learning Class? An Elective Course “Kansei Engineering in Affective Design” - Habyba, Anik Nur; Safitri, Dian Mardi; Rahmawati, Novia; Sari, Indah Permata; Utami, Ika Wahyu (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Research-based elective courses can be an alternative to Student-Centered Learning (SCL) classes. Project-based learning (PjBL) can be an attractive learning method. PjBL was developed through lecturers' research interests to balance the tri dharma of higher education. This study aims to give an example of creating an elective course in an SCL class. Kansei Engineering in Affective Design (KEiAD) class is a PjBL elective course successfully implemented in the Industrial Engineering Department of Universitas Trisakti by appointing the lecturer's research. Course learning outcome (CLO) was developed through five major stages of the KEiAD framework: identifying Kansei users, selecting design concepts, identifying key design elements, formulating design, and prototyping. The first lecture had good results. Eleven groups containing two to three students could formulate 11 affective products. All students also succeeded in achieving the expected outcomes of this course. Several students showed interest in using KEiAD as a final project topic. In the future, a quota for elective courses that is too large, such as 32 students, is considered too large because the assistance in class is not intensive enough. Smaller student quotas and R studio alternatives can be considered for continuous improvement.